Endothelial Nitric Oxide Synthase Gene Polymorphisms (− 922A > G, − 786 T > C, Intron 4 b/a VNTR and 894 G > T) and Essential Hypertension: An Association Study with Haplotypes Analysis - Farbood, Zahra; Sabeti Aghabozorgi, Amirsaeed; Nejatizadeh, Azim; Farshidi, Hossein; Shams, Leila; Bahreyni, Amirhossein; Mansouri Babamansouri, Elahe; Shekari, Mohammad (Biochemical genetics, 2020)
Endothelial Nitric Oxide Synthase (eNOS) is an indispensable regulator of blood pressure through producing Nitric Oxide (NO). There is some evidence to suggest that eNOS gene polymorphisms are associated with Essential Hypertension (EHT). In this study, the potential association between eNOS 4a/4b, A922G, G894T, T786C gene polymorphisms and EHT as individual risk factors and as haplotypes are examined in the southern population of Iran (Bandar-Abbas). In this study, 200 EHT patients and 200 normotensive subjects which were matched for age and sex were included. Genotyping was performed by either utilizing Polymerase Chain Reaction (PCR) or PCR followed by Restriction Fragment length Polymorphism (RFLP) method. Our results demonstrated statistically significant associations between T786C, G894T, and 4a/4a and EHT ( p < 0.05); however, A922G had no significant association with EHT ( p > 0.05). Haplotype analysis also suggested that − 786C/− 922A/4a, − 786C/− 922A/4b and − 786C/− 922G/4a haplotypes were more frequent in EHT group than control group, hypothesizing a positive association with EHT. The present study has identified that the eNOS genetic variations are associated with EHT in southern population of Iran (Bandar-Abbas). These findings also suggested that a number of haplotypes of eNOS gene may be a driving factor for EHT susceptibility in respected population.